THE LAW OF THE INSEPARABLE CONNECTION OF THE DUALITY OF SYSTEMS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article examines the nature and essence of the concept of “system”. A new law of inextricable connection between the material and immaterial duality of systems is established. It is emphasized that this law operates in all spheres: physical, biological and social systems. It belongs to the category of universal laws of nature
Keywords: systems, structure, elements, form of existence, triad, law.